2020
DOI: 10.1002/jmv.26349
|View full text |Cite
|
Sign up to set email alerts
|

Detection profile of SARS‐CoV‐2 using RT‐PCR in different types of clinical specimens: A systematic review and meta‐analysis

Abstract: Testing is one of the commendable measures for curbing the spread of coronavirus disease (COVID‐19). But, it should be done using the most appropriate specimen and an accurate diagnostic test such as real‐time reverse transcription‐polymerase chain reaction (qRT‐PCR). Therefore, a systematic review was conducted to determine the positive detection rate of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) in different clinical specimens using qRT‐PCR. A total of 8136 pooled clinical specimens were an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
174
0
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 202 publications
(196 citation statements)
references
References 24 publications
(66 reference statements)
7
174
0
6
Order By: Relevance
“…www.nature.com/scientificreports/ specimens probably influence the detection rate of recurrent positivity. As previously reported in a systematic review, the positive rate (PR) for nasopharyngeal swab, fecal, and oropharyngeal swab were 45.5%, 32.8%, and 7.6%, respectively 23 , with the highest reported detection rate being from specimens collected from the bronchoalveolar lavage fluid (PR of 92%) 23 . None of the studies included in our meta-analysis had collected samples from bronchoalveolar lavage fluid.…”
Section: Discussionmentioning
confidence: 56%
“…www.nature.com/scientificreports/ specimens probably influence the detection rate of recurrent positivity. As previously reported in a systematic review, the positive rate (PR) for nasopharyngeal swab, fecal, and oropharyngeal swab were 45.5%, 32.8%, and 7.6%, respectively 23 , with the highest reported detection rate being from specimens collected from the bronchoalveolar lavage fluid (PR of 92%) 23 . None of the studies included in our meta-analysis had collected samples from bronchoalveolar lavage fluid.…”
Section: Discussionmentioning
confidence: 56%
“…In contrast to other review studies concerning SARS-CoV-2 which included only 5, 7, and 11 articles in the quantitative synthesis, our study utilized 14 articles to support the result and ensure a firm conclusion between saliva and NPS specimens in detecting COVID-19. 34 , 35 , 36 Moreover, since there is still limited data on COVID-19, this review study did not take other factors, such as other specimens and severity of disease or others diagnostic techniques into account. Further studies should address these issues.…”
Section: Discussionmentioning
confidence: 99%
“…Recent systematic reviews and meta-analyses of the current peer-reviewed and preprint literature confirm fecal SARS-CoV-2 viral RNA detection in roughly half of COVID-19 patients ( Gupta et al, 2020 ; Parasa et al, 2020 ). Moreover, a systematic review and meta-analysis of SARS-CoV-2 viral RNA detection profiles in several different types of COVID-19 patient specimens found that positive detection rates were higher in rectal and sputum swabs than in the commonly used NP swab ( Bwire et al, 2020 ). These data provide a clear rationale to probe wastewater for SARS-CoV-2 RNA.…”
Section: Introductionmentioning
confidence: 99%